Hypoxemic Respiratory Failure from Acute Respiratory Distress Syndrome Secondary to Leptospirosis. (12th October 2017) - Fernando, Shannon M.; Cardinal, Pierre; Brindley, Peter G.
Abstract : Acute respiratory distress syndrome (ARDS), characterized by hypoxemic respiratory failure, is associated with a mortality of 30–50% and is precipitated by both direct and indirect pulmonary insults. Treatment is largely supportive, consisting of lung protective ventilation and thereby necessitating Intensive Care Unit (ICU) admission. The most common precipitant is community-acquired bacterial pneumonia, but other putative pathogens include viruses and fungi. On rare occasions, ARDS can be secondary to tropical disease. Accordingly, a history should include travel to endemic regions. Leptospirosis is a zoonotic disease most common in the tropics and typically associated with mild pulmonary complications. We describe a case of a 25-year-old male with undiagnosed leptospirosis, presenting with fever and severe hypoxemic respiratory failure, returning from a Costa Rican holiday. There was no other organ failure. He was intubated and received lung protective ventilation. His condition improved after ampicillin and penicillin G were added empirically. This case illustrates the rare complication of ARDS from leptospirosis, the importance of taking a travel history, and the need for empiric therapy because of diagnostic delay.